2006
DOI: 10.2337/dc06-1550
|View full text |Cite
|
Sign up to set email alerts
|

Patient Interpretation of Neuropathy (PIN) Questionnaire

Abstract: OBJECTIVE -Using the common-sense model of illness behavior, we developed and validated a self-report instrument for assessment of patients' cognitive and emotional representations of diabetic peripheral neuropathy (DPN) influencing foot self-care. RESEARCH DESIGN AND METHODS -The PatientInterpretation of Neuropathy (PIN) questionnaire, generated from discussions with clinicians and interviews with patients with DPN, was administered to patients with DPN attending U.K. (n ϭ 325) and U.S. (n ϭ 170) diabetes cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 29 publications
6
90
0
1
Order By: Relevance
“…This observation is consistent with previous work, which has shown that patients with chronic disease often hold beliefs about the likely cause, course, and management of their condition that differ from the medical disease model. [32][33][34][35] Medically unorthodox beliefs have also been observed in lay views of drugs and medicines. 36 There were indications in this study that participants sometimes deliberately decided to disregard foot-care advice from professionals if it contradicted their personal beliefs (for example, in relation to sometimes walking barefoot).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This observation is consistent with previous work, which has shown that patients with chronic disease often hold beliefs about the likely cause, course, and management of their condition that differ from the medical disease model. [32][33][34][35] Medically unorthodox beliefs have also been observed in lay views of drugs and medicines. 36 There were indications in this study that participants sometimes deliberately decided to disregard foot-care advice from professionals if it contradicted their personal beliefs (for example, in relation to sometimes walking barefoot).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…A few previous studies have reported similar findings and that patients sometimes blame health professionals after foot ulceration has occurred. 35,38 It is a matter of concern that most participants in this study were unaware of the connection between breaks in the skin, foot ulceration, and amputation. There is good evidence that the single most important thing that can be done by people with diabetesparticularly older people who are more likely to have developed micro-and macrovascular disease -to prevent foot ulceration is to protect their feet from any cuts, sores, blisters, or cracked skin.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…It is well known that patients’ mental models of DF disease, including their experiences and interpretations of causes and mechanisms, influence their behaviors and what actions they take [79]. For example, patients who have had a minor amputation or think that wearing therapeutic shoes is important to prevent complications report higher adherence to wearing therapeutic shoes [10,11], while patients who think that they cannot prevent foot ulcers report lower preventive foot self-care [12].…”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de los estudios han sido desarrollados a partir del "Illness Perception Questionnaire" donde se ha evaluado su relación especialmente con CVRS en pacientes con enfermedades cróni-cas como: insuficiencia renal crónica (Fowler & Baas, 2006), osteoartritis (Botha-Scheepers et al, 2006), neuropatía periférica diabética (Vileikyte et al, 2006), cáncer de cabeza y cuello (Scharloo et al, 2005), VIH (Henderson, Safa, Easterbrook & Hotopf, 2005).…”
Section: Introductionunclassified